Adsorption behavior of levulinic acid onto microporous hyper-cross-linked polymers in aqueous solution: Equilibrium, thermodynamic, kinetic simulation and fixed-bed column studies. (March 2017) - Lin, Xiaoqing; Huang, Qianlin; Qi, Gaoxiang; Xiong, Lian; Huang, Chao; Chen, Xuefang; Li, Hailong; Chen, Xinde
Abstract: The recovery of levulinic acid (LA) from aqueous solution and actual biomass hydrolysate by a microporous hyper-cross-linked polymer, SY-01, was investigated for the first time under batch and fixed-bed column conditions. The results showed that the optimum pH should be in the acidic range (pH < 3.0) without adjusting the pH. In the single-component system equilibrium study, the Langmuir isotherm model fits the LA adsorption onto SY-01 resin better than the Freundlich isotherm model, indicating that LA adsorption onto SY-01 resin under the concentration range studied is a monolayer homogeneous adsorption process. The maximum adsorption capacity of LA onto SY-01 resin decreased with increasing temperature, ranging from 103.74 to 95.70 mg/g. The obtained thermodynamic parameters suggested that the adsorption of LA on SY-01 was spontaneous ( ΔG 0 <−3.788 kJ/mol), and exothermic ( ΔH 0  = −11.764 kJ/mol). For kinetic study, the adsorption of LA onto SY-01 resin at various operating conditions follows the pore diffusion model and the intraparticle diffusion is the rate-limiting step for the adsorption of LA onto SY-01 resin. The effective pore diffusivity was dependent upon temperature, but independent of initial LA concentration, and were 3.306 × 10 −10, 5.274 × 10 −10 and 7.707 × 10 −10  m 2 /s at 298, 318 and 338 K, respectively. In desorption process, the recovery efficiency of LA from SY-01 resin was 99.39%, and LA concentration in the eluent was raised 2.97-fold. In conclusion, our results show that the SY-01 resin has potential application in product recovery of LA from biomass hydrolysate. Graphical abstract: Highlights: The feasibility of LA separation by a hyper-crossed-linked polymer was verified. The equilibrium, kinetic and thermodynamic properties of LA adsorption was studied. The process of LA from actual biomass hydrolysate was studied for the first time. The concentration of LA in the eluent was increased by 2.97 folds.